Caffeine mouth rinse plus ingestion improves the 10-km time trial compared to caffeine mouth rinse alone - Marinhoa, A. H.; da Silva, J. M.; Brandão, V. F. N.; Jatobá, S. G.; Balikian Júnior, P.; Ataide-Silva, T.; de Barros Sousa, F. A.; Bastos-Silva, V. J.; de Araujo, G. G. (Research Quarterly for Exercise and Sport, 2024)
Background The benefits of caffeine to physical performance have been extensively demonstrated, however, it has recently been speculated that there is an effect of the administration route on its effectiveness.